Clinical relevance of intradermal test results in atopic dogs - Mallmann, Stefanie; Klinger, Christoph J.; Claßen, Janine; Wagner, Iris; Klima, Andre; Castelletti, Noemi; Müller, Ralf S. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2021)
Topic and aims Canine atopic dermatitis (AD) is an inflammatory and pruritic skin disease and in most cases associated with IgE antibodies against environmental allergens. To date, the only causative therapeutic option is allergen immunotherapy (AIT). Offending allergens for AIT can be identified by intradermal testing (IDT) or serum allergen-specific IgE testing. The aim of the study was to evaluate positive IDT results considering the atopic dogs’ clinical history.Material and methods An IDT was performed on 48 atopic dogs and their owners completed a detailed questionnaire about the seasonal course of their pruritus. Results of IDT were correlated with the seasonal occurrence of pruritus.Results The most common positive IDT reactions were observed to mite allergens (33.3–62.5 %). Prevalence of positive reactions to individual tree, grass and weed pollen ranged between 8.3 % and 25 %. Moulds and epithelial allergens produced positive reactions in only 0–6.3 %. A correlation between positive IDT reactions and course of pruritus could neither be found for perennial nor for seasonal allergens.Conclusion The evaluation of IDT reactions may not be an optimal method for identification of clinically relevant allergens in canine AD.Clinical relevance The results of this study emphasise the importance of considering clinical history in addition to allergy test results in the formulation of an allergen extract for desensitisation.
Keywords: Allergy; atopy; canine; dermatitis; intradermal testing; pruritus